การเมืองว่าด้วยการต่อสู้ทางชนชั้นในประเทศไทยจาก พ.ศ.2535 ถึง พ.ศ.2549 - เก่งกิจ กิติเรียงลาภ (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
My finding is that since 1992 there have been three major social forces (the monarchy, new capitalists and people’s movements) shaping dynamics and changes in the state and civil society in Thailand. More significantly, since the 1997 economic crisis, the monarchy as the most powerful political institution has established its royal hegemony by assimilating and allying with various groups of the other social forces such as public intellectuals, political activists, NGOs, high-ranking bureaucrats, new generation capitalists and the state apparatuses. In this thesis, I propose to call this very establishing cross-class alliance, in Gramscian term, as "the nationalist-communitarian historic bloc with the leadership of the monarchy". Ideologically, the historic bloc contains various discourses of different social classes such as nationalism, communitarianism, anti-capitalism, clean politics and self-sufficien economy. As a result of this establishment, the rise and fall of the Thai Rak Thai government could not take place without political and ideological supports from the historic bloc comprising the monarchy and people’s movements.